Index of Caries Experience - A Composite System for Recording Dental Caries - Sreevidya Bhat; Meghashyam Bhat (Wolters Kluwer Medknow Publications, 2024)
Introduction: Measurement of dental caries is imperative for its prevention and control. The present study was conducted with the aim of developing a dental caries index that is reliable, reversible, and valid. A cross-sectional study was designed and conducted at the outreach dental clinics of a dental school in India. Methods and Material: A total of 219 patients visiting outreach centres participated in the study. Patients attending outreach dental clinics aged 15 years and above, who were dentate and affected by dental caries, were included. Clinical examination was done under clinical conditions with dental chair lighting. Decayed Missing and Filled Teeth (DMFT) and Index of Caries Experience (ICE) were recorded using the visuo-tactile method according to the index criteria. Results: The relationship between the DMFT and ICE was determined. Results showed that the DMFT from ICE had good correlation. The decayed teeth index (DTI) score varied from decayed teeth (DT) according to age and sex. DTI was significantly higher for females than for males and higher among younger age groups than older ones, but DT did not exhibit the differences. Conclusions: ICE is a new system in which the proviso is to measure the non-cavitated lesions and health of permanent dentition. DMFT and ICE have good correlation. DTI is more sensitive than the DT score.